Glycoprotein IIb/IIIa Inhibitors Use and Outcome after Percutaneous Coronary Intervention for Non-ST Elevation Myocardial Infarction. (8th May 2014) - Howard, J. P.; Jones, D. A.; Gallagher, S.; Rathod, K.; Antoniou, S.; Wright, P.; Knight, C.; Mathur, A.; Weerackody, R.; Wragg, A.
Abstract : Aims . We investigate the effect of glycoprotein IIb/IIIa (GP IIb/IIIa) inhibitors on long-term outcomes following percutaneous coronary intervention (PCI) after non-ST elevation myocardial infarction (NSTEMI). Meta-analyses indicate that these agents are associated with improved short-term outcomes. However, many trials were undertaken before the routine use of P2Y12 inhibitors. Recent studies yield conflicting results and registry data have suggested that GP IIb/IIIa inhibitors may cause more bleeding than what trials indicate. Methods and Results . This retrospective observational study involves 3047 patients receiving dual-antiplatelet therapy who underwent PCI for NSTEMI. Primary outcome was all-cause mortality. Major adverse cardiac events (MACE) were a secondary outcome. Mean follow-up was 4.6 years. Patients treated with GP IIb/IIIa inhibitors were younger with fewer comorbidities. Although the unadjusted Kaplan-Meier analysis suggested that GP IIb/IIIa inhibitor use was associated with improved outcomes, multivariate analysis (including propensity scoring) showed no benefit for either survival (P = 0.136 ) or MACE (P = 0.614 ). GP IIb/IIIa inhibitor use was associated with an increased risk of major bleeding (P = 0.021 ). Conclusion . Although GP IIb/IIIa inhibitor use appeared to improve outcomes after PCI for NSTEMI, patients who received GP IIb/IIIa inhibitors tended to be at lower risk. After multivariate adjustment we observed no improvement in MACE or survival and an increased risk of major bleeding.